2014
DOI: 10.1159/000361045
|View full text |Cite
|
Sign up to set email alerts
|

Uhthoff's Phenomenon in Multiple Sclerosis and Neuromyelitis Optica

Abstract: To evaluate and compare the incidence and clinical features of Uhthoff's phenomenon in Japanese patients with neuromyelitis optica (NMO) and those with multiple sclerosis (MS), we asked 135 consecutive patients with MS and an NMO-related disorder (NMOrd) whether they experienced worse neurological symptoms after an increase in body temperature. Responses were obtained from 54 MS and 37 NMOrd patients. Uhthoff's phenomenon was observed in 26 MS (48.1%) and 20 NMOrd patients (54.1%). Motor and sensory symptoms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…It was present in 50% of our sample, with no difference between groups. This prevalence is similar to another study which reported it in 48.1% of the subjects with NMO, compared to 54.1% of those with MS (Park et al, 2014). A lower prevalence of Uhthoff was described in another study in 2015: only 27.1% of the NMO subgroup (Muto et al, 2015).…”
Section: Graphic 4 -Changes In Edss (A) Bpi Intensity (B) Bpi Intersupporting
confidence: 89%
See 1 more Smart Citation
“…It was present in 50% of our sample, with no difference between groups. This prevalence is similar to another study which reported it in 48.1% of the subjects with NMO, compared to 54.1% of those with MS (Park et al, 2014). A lower prevalence of Uhthoff was described in another study in 2015: only 27.1% of the NMO subgroup (Muto et al, 2015).…”
Section: Graphic 4 -Changes In Edss (A) Bpi Intensity (B) Bpi Intersupporting
confidence: 89%
“…Concomitant sensory and motor symptoms were the most frequent symptoms, followed by visual disturbances (Park et al, 2014). Another study described that 27.1% of the NMO subgroup presented this phaenomenon (Muto et al, 2015).…”
Section: "Non-motor" Symptoms In Nmomentioning
confidence: 94%
“…Despite the early surgical interventions for the cervical and thoracic spine, the patient’s muscle strength in the lower extremities temporarily decreased. It has been reported that increased body temperature may deteriorate neurological symptoms in MS and NMOSD (Uhthoff phenomenon) [ 18 , 19 , 20 ]. Since there was no direct injury of the spinal cord during surgeries, postoperative fever or inflammation may have caused a temporary exacerbation of neurological symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…18 The UP is typically encountered in MS but appears in other demyelinating conditions such as Neuro Myelitis Optica (NMO). 19 Until recently, NMO was considered a subtype of MS due to a similar clinical presentation. However, in 2004 upon the publication on the association between NMO and an antibody against aquaporin 4 (anti-AQP4 Ab) or NMO-IgG, NMO started being considered a different disease.…”
Section: Discussionmentioning
confidence: 99%